2016
DOI: 10.1021/acs.chemmater.6b03669
|View full text |Cite
|
Sign up to set email alerts
|

Sn(II)-Containing Phosphates as Optoelectronic Materials

Abstract: We theoretically investigate Sn(II) phosphates as optoelectronic materials using first principles calculations. We focus on known prototype materials SnnP2O5+n (n=2, 3, 4, 5) and a previously unreported compound, SnP2O6 (n=1), which we find using global optimization structure prediction. The electronic structure calculations indicate that these compounds all have large band gaps above 3.2 eV, meaning their transparency to visible light. Several of these compounds show relatively low hole effective masses (∼2-3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…The study clearly indicates the difficulty to find high-mobility p-type oxides due to the 42,99 Further computational exploration of the Sn 2+ and Pb 2+ chemistries was also performed by Singh et al focusing on alkali-earth and phosphates. [100][101][102] Bhatia et al 103 extended this HT screening to quaternary oxides. The screening identified Ba 2 BiTaO 6 as a p-type TCO candidate.…”
Section: Ht Approachmentioning
confidence: 99%
“…The study clearly indicates the difficulty to find high-mobility p-type oxides due to the 42,99 Further computational exploration of the Sn 2+ and Pb 2+ chemistries was also performed by Singh et al focusing on alkali-earth and phosphates. [100][101][102] Bhatia et al 103 extended this HT screening to quaternary oxides. The screening identified Ba 2 BiTaO 6 as a p-type TCO candidate.…”
Section: Ht Approachmentioning
confidence: 99%
“…Explicit formulas are given for the rhombohedral case. Our approach is fully suited also for triclinic materials that seem to become interesting in the field of p‐type transparent conductive oxides, namely Sn 5 P 2 O 10 [ 9 ] or Sn 2 GeO 4 . [ 10 ] The procedure can be easily transferred to a symbolic math program.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a wealth of literature is focused on HT computational screening and discovery of p-type TCMs. 25,[157][158][159][160][161][162][163][164][165][166] Especially, a set of 18 valence electron ternary ABX compounds (with 1:1:1 stoichiometry) were identified as promising p-type TCMs. 37,167 Based on the HT DFT calculations, Ran et al 168 potential p-type TCOs, among which the p-type dopability was found to be promisingly feasible for the compounds with larger n value.…”
Section: Transparent Conducting Materialsmentioning
confidence: 99%
“…calculated the band gap, effective mass of electrons and holes, and optical absorption of a series of bismuth/antimony oxyhalides and chalcohalides to screen out BiOCl/Br, SbOF, and Sb 4 O 5 Cl 2 / Br 2 as potential p-type TCMs. Xu et al162 identified the Sn(II)-containing compounds Sn n P 2 O 5 + n (n = 1, 2, 3, 4,5) asF I G U R E 4The virtual and experimental discovery pipeline for design of molecular organic light-emitting diodes (OLEDs) (left): The search space was reduced from six orders of magnitude to one. The cubes represent the size of search space at each stage.…”
mentioning
confidence: 99%